ANALYSIS OF STUDENT'S RATIONAL THINKING ABILITY IN A CAREER PERSPECTIVE IN THE FIELD OF SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS (STEM) - Putri, Ersa Amalia; Fadly, Wirawan (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
The ability to think rationally is the ability that a person has based on real events so that he is able to solve problems with a reasonable mindset that can be accepted by reason. The STEM approach is an approach that combines four fields of science, namely Science, Technology, Engineering, and Mathematics which is interesting to apply in science learning, which is able to provide experience and lead to career fields. This study aims to determine the students' rational thinking skills towards the career perspective of the STEM field. The research method used is a qualitative method with the type or design of naturalistic research. Data were collected by observation, documentation and in-depth interviews (In Depth Interview) which were conducted on 7 selected informants. The data that has been obtained is then analyzed using the Miles & Huberman model which consists of three stages, namely 1) Data Reduction 2) Data Presentation 3) And Drawing Conclusions, research analysis is assisted by Nvivo12 Software for the coding process to determine the category of rational thinking skills and answers that according to the interview. Based on the results of data analysis shows that students have a tendency to be creative in processing a product with the ability to imagine and the ability to imagine that applies the ability to imagine and imagine. Students have a tendency to have a career in the fields of Science, Engineering and Technology so that students have the desire to have a career in the biotechnoplaner field.